2003
DOI: 10.1002/bdd.358
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of modified‐release methylphenidate: influence of high‐fat breakfast when administered intact and when capsule content sprinkled on applesauce

Abstract: Ritalin, an immediate release form of racemic methylphenidate hydrochloride, has been available in the USA since 1955 and is used for the treatment of ADHD. The objective of this study was to evaluate the pharmacokinetics of modified-release methylphenidate (highest single dose), Ritalin LA, when administered under fasting condition, with a high-fat breakfast, and when sprinkled on applesauce in healthy adult subjects. Blood samples were drawn for 24 h following a 40 mg oral administration. Most subjects appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
19
1

Year Published

2003
2003
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 15 publications
4
19
1
Order By: Relevance
“…The twopeak plasma concentration-time profiles are very similar to that reported previously conducted under similar experimental conditions in adults [11][12][13] and in children [11]. The C max and AUC values in the present study (40 mg) are also similar to those reported previously at a lower dose 20 mg [11] after correction for the dose differences.…”
Section: Resultssupporting
confidence: 92%
“…The twopeak plasma concentration-time profiles are very similar to that reported previously conducted under similar experimental conditions in adults [11][12][13] and in children [11]. The C max and AUC values in the present study (40 mg) are also similar to those reported previously at a lower dose 20 mg [11] after correction for the dose differences.…”
Section: Resultssupporting
confidence: 92%
“…This trial thus corroborates the pharmacokinetic studies, which pointed out the potential advantage for Ritalin Ò LA of not being influenced by food intake (Lee et al 2003;Haessler et al 2008). Remarkably, this independence of food has been confirmed by several raters in different categories that often have a different view of medication effects: teachers, parents and physicians independently agreed that there is no difference in efficacy regardless of the breakfast group.…”
Section: Discussionsupporting
confidence: 77%
“…For Ritalin Ò LA, it has been shown that a high-fat breakfast has only a negligible effect on the bioavailability when compared to a standard breakfast (Lee et al 2003). In a previous study, comparing the pharmacokinetics of Ritalin Ò LA and Medikinet Ò retard, it could be shown that Ritalin Ò LA exerted its biphasic profile under both fasted and fed conditions with a standard continental breakfast, while Medikinet Ò retard lost the retardation in the fasted state (Haessler et al 2008).…”
Section: Introductionmentioning
confidence: 97%
“…10,136 Ritalin LA capsules can be opened and sprinkled on applesauce if needed without altering the pharmacokinetic profile. 139 Ritalin LA may be given without regard to food, although, as with the other modified-release MPH formulations, high-fat meals may delay the T max by approximately 1 hour. The overall extent of absorption is not significantly affected by food.…”
Section: Modified-release Technologiesmentioning
confidence: 99%
“…The overall extent of absorption is not significantly affected by food. 139 Ritalin LA is available in 20-, 30-, and 40-mg capsule strengths (Table 3).…”
Section: Modified-release Technologiesmentioning
confidence: 99%